Evaluation of uptake and attitude to voluntary counseling and testing among health care professional students in Kilimanjaro region, Tanzania - Nkya Hassan M; Shekalaghe Seif; Barongo Longin R; Mahande Aneth M; Kweka Eliningaya J; Charles Mgosha P; Lowassa Asanterabi; Mahande Michael J (BMC, 2009)
Abstract Background Voluntary counseling and testing (VCT) is a corner stone for successful implementation of prevention, care and support services among HIV negative and positive individuals. VCT is also perceived to be an effective strategy in risk reduction among sexually active young people.. This study aimed to assess the acceptability of VCT and its actual uptake among young health care professional students at KCM College of Tumaini University and Allied health schools. Methods This was a cross-sectional study. A structured questionnaire was used among health care professional students aged 18-25 years who were enrolled in degrees, diplomas and certificates courses at Kilimanjaro Christian Medical College and all other Allied health schools Results A total of 309 students were recruited, among these 197 (63.8%) were females. All respondents were aware of the benefits of VCT. Only 107 (34.6%) of students have had VCT done previously. About 59 (19.1%) of the students had negative for health care professional to attend VCT. Risk perception among the students was low (37.2%) even though they were found to have higher risk behaviors that predispose them to get HIV infection. Conclusion Awareness of VCT services and willingness to test is high among students; however its uptake is low. In order to promote these services, a comprehensive training module on VCT needs to be included in their training curricula. In particular, more emphasis should focus on the benefits of VCT and to help the students to internalize the risk of HIV so that they can take preventive measures.